Bringing tax avoiders to light: Moral framing and shaming in a public goods experiment - Stefanos A. Tsikas; Andreas Wagener (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
With a series of public goods games in a 2x2-design, we analyze two channels that might moderate social dilemmas and increase cooperation without using pecuniary incentives: moral framing and shaming. Cooperation increases when non-contributing to a public good is framed as morally debatable and socially harmful tax avoidance. However, cooperation is only durable when free-riders are "shamed" by disclosing their misdemeanor. We find shaming effects to be strong enough to make appeals to morality redundant for participants' decisions.
Keywords: E62; H26; H30; 330; Shaming; framing; tax avoidance; public goods experiment